PUSAT RESTORASI EKOSISTEM: PENGEMBALIAN ALAM - Heni Sofyani; Suwandi Supatra (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Millenials  who is biological species continues to live in  artificial machine cities.  The needs of modern man invaded  the urban with buildings left no space for natural settings. Noticed that peoples started to plant trees one dear for living with nature : see, touch, feel, and be part of them. Indonesia is a country with the second longest coastal line in the world, but nowadays people aren’t take good care of the sea some bad phenomenon really happened particularly in the central city of Indonesia, Jakarta. In Ancol people throwing waste, the industry waste contaminated the sea and in result the sea ecosystem is unstable. The project Ecosystem Restoration Center in Ancol, Jakarta Utara with a purpose when this project is being built people can change their perspective on how to treat and in  contact with nature. Phenomenology and arhitecture types as a method to design this building, the result of theproject appear as the solution for millenials in the invaded city, an injection for balancing and perhaps regenerating the ecosystem of air, ground and sea. A fun and relax space for public realm to retrieve their dear of  nature, for them to exchange and shape a new then better behavior of them toward on how to treat and in contact the nature. Abstrak Milenial merupakan spesies biologis yang hidup di kota-kota ‘buatan’. Kebutuhan manusia modern sangat kompleks ruang kota berisi bangunan- bangunan dan tidak menyisakan ruang untuk alam/ area hijau. Memperhatikan bahwa orang-orang mulai membuat jalur hijau sebagai tanda bahwa mereka ingin hidup berdampingan dengan alam: melihat, menyentuh, merasakan, dan menjadi bagian dari alam. Indonesia adalah negara dengan garis pantai terpanjang kedua di dunia, tetapi saat ini manusia tidak merawat laut dengan baik, beberapa fenomena buruk benar-benar terjadi terutama di pusat kota Indonesia, Jakarta. Di Ancol orang membuang sampah sembarangan, limbah industri mencemari laut dan akibatnya ekosistem laut menjadi tidak stabil. Proyek Pusat Restorasi Ekosistem yang terletak di Ancol, Jakarta Utara ini bertujuan untuk mengubah perspektif manusia tentang cara merawat dan berinteraksi dengan alam. Penggunaan fenomenologi dan tipologi arsitektur sebagai metode untuk merancang bangunan ini, hasil proyek ini berupa solusi untuk milenial, injeksi untuk penyeimbangan dan meregenerasi ekosistem udara, darat dan laut. Ruang yang menyenangkan dan rileks bagi ranah publik untuk kembali bersama alam, ruang untuk bertukar dan membentuk perilaku baru yang lebih baik mengenai cara memperlakukan dan berhubungan dengan alam.